OPTICAL TRANSPARENT electromagnetic shields - A. T. Volochko; V. A. Zelenin; G. V. Markov; E. O. Narushko (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The examples of transparent electromagnetic high-efficiency screening shields have been analyzed, the results of measuring the screening efficiency of engineering designs consisting of a glass base and a multilayer metal-ceramic coating have been presented.